Exposure assessment to fumonisins B1, B2 and B3 through consumption of gluten-free foodstuffs intended for people affected by celiac disease. (November 2016) - Esposito, Francesco; Fasano, Evelina; Scognamiglio, Gelsomina; Nardone, Antonio; Triassi, Maria; Cirillo, Teresa
Abstract: Fumonisins are mycotoxins produced by Fusarium species and affecting maize crops. Some analogues of fumonisins are known for their toxic and possible carcinogenic effects on humans and animals. Because of their occurrence in corn-based food, diet is the main source of exposure to these mycotoxins, especially among people affected by celiac disease. Hence, the purpose of this paper was to evaluate the amount of fumonisins B1, B2 and B3 in maize-based products and to assess the exposure of people affected by celiac disease to fumonisins. The sample consisted of 154 gluten-free products analyzed according to method UNI EN 14352:2005. Results showed a heterogeneous contamination by fumoninisin B1, B2 and B3, although below limits of Commission Regulation No 1126/2007 and consistent with other European literature data. Exposure to fumonisins was evaluated for different age groups. In some cases exposure to fumonisins could not be ignored since the total intake could exceed EFSA Provisional Maximum Tolerable Intake up to 150%. Therefore, in the light of an overall contamination by fumonisins the total dietary exposure could be underrated not only in people affected by celiac disease, but also in non-celiac population. Highlights: 154 gluten-free products were analyzed according to method UNI EN 14352:2005. Results showed a diffuse contamination by fumoninisins, although below European regulation limits. People affected by celiac disease could show, in some cases, a high dietary exposure. Exposure to fumonisins could be underestimated also in healthy peers.